2015
DOI: 10.3892/or.2015.4255
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the differential secretome of nasopharyngeal carcinoma cell lines CNE-2R and CNE-2

Abstract: Radioresistance is the major cause of poor prognosis in nasopharyngeal carcinoma (NPC). To identify and characterize the secretome associated with NPC radioresistance, we compared the conditioned serum-free medium of radioresistant CNE-2R cells with that of the parental radiosensitive CNE-2 cells using isobaric tags for relative and absolute quantitation (iTRAQ) with liquid chromatography-electrospray tandem mass spectrometry (LC-ESI-MS/MS) quantitative proteomics. Before proceeding to quantitative proteomics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…To identify biological markers that can predict the response of NPC to radiotherapy, in a previous study, we analyzed the profiles of secretory proteins in NPC cell lines with variable radiosensitivities using the quantitative iTRAQ method [ 8 ]. The resultant data identified 26 differentially secreted proteins, including QSOX1, that displayed a dramatic difference in expression between the radiosensitive and radioresistant NPC cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify biological markers that can predict the response of NPC to radiotherapy, in a previous study, we analyzed the profiles of secretory proteins in NPC cell lines with variable radiosensitivities using the quantitative iTRAQ method [ 8 ]. The resultant data identified 26 differentially secreted proteins, including QSOX1, that displayed a dramatic difference in expression between the radiosensitive and radioresistant NPC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultured in RPMI-1640 medium (HyClone, Logan, UT, USA) supplemented with 10% fetal bovine serum (Gibco, Grand Island, NY, USA) and 1% penicillin/streptomycin (Beyotime Bio, China) (100 μg /mL), at 37°C in a humidified incubator with 5% CO 2 . The preparation of conditioned media (CM) was performed as previously described [ 8 ]. For lentiviral infection, CNE-2 cells were cultured with QSOX1-shRNA-encoded lentivirus (QSOX1-shRNA group) or empty vector-encoded lentivirus (NC group) at a multiplicity of infection (MOI) of 40 for 48 h. To assess the transduction efficiency, the expression of GFP was evaluated using an inverted fluorescence microscope (Olympus, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteomic technology is an effective method to search for effective serum biomarkers. In previous studies [ 7 ], some differentially secreted proteins were identified by proteomic techniques. CD166 is one of the 26 differentially secreted proteins, which is of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of differentially expressed proteins by proteomic methods is an effective and widely used technique [ 6 ]. In previous studies [ 7 ], the radioresistant CNE-2R and its parental CNE-2 cell line were cultured in vitro . Some differentially secreted proteins were identified by proteomic techniques, and CD166 is one of them.…”
Section: Introductionmentioning
confidence: 99%